COMPARISON OF THE OUTCOME OF DESCENDING DIVIDED VERSUS SIGMOID LOOP COLOSTOMY IN PATIENTS WITH ANORECTAL MALFORMATION (The Research of Medical Science Review, 2025)
Objective: To compare the outcomes of descending divided versus sigmoid loop Jcolostomy in neonates with anorectal malformations (ARM) in terms of stoma prolapse, retraction, and parastomal hernia. Methodology: This randomized controlled trial was conducted at the Department of Pediatric Surgery, Sahiwal Teaching Hospital, over eleven months. A total of 280 neonates with ARM were randomly assigned into two groups: Group A (descending divided colostomy) and Group B (sigmoid loop colostomy), with 140 patients in each group. Patients were monitored for complications including stoma prolapse, retraction, and parastomal hernia for 30 days post-surgery. Results: The incidence of stoma prolapse was 9.8% in Group A and 10.2% in Group B (p = 0.905). Stoma retraction occurred in 2.8% of Group A and 4.4% of Group B (p = 0.476), while parastomal hernia rates were 1.4% in Group A and 2.2% in Group B (p = 0.617). Conclusion: Both descending divided and sigmoid loop colostomies are equally safe and effective for managing ARM, but no remarkable statistical difference was recorded.